2013
DOI: 10.1002/ptr.5089
|View full text |Cite
|
Sign up to set email alerts
|

Trametenolic Acid B Reverses Multidrug Resistance in Breast Cancer Cells Through Regulating the Expression Level of P‐Glycoprotein

Abstract: Trametenolic acid B (TAB) is the main active composition of Trametes lactinea (Berk.) Pat which possesses antitumor activities. There was no report its antitumor effect through regulating P-glycoprotein (P-gp) so far, due to P-gp over expression is one of the most important mechanisms contributing to the multiple drug resistance phenotype. The present aim was to investigate the effects of TAB on P-gp in multidrug-resistant cells; Paclitaxel-resistant cell line MDA-MB-231/Taxol was established by stepwise expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…10,34) Cytotoxic effect of morin treated as a mixed micelle formulation was significantly increased compared with that of morin alone (Fig. 7A), suggesting the synergistic role of PluronicF127 and Tween80 as P-gp modulators.…”
Section: Discussionmentioning
confidence: 98%
“…10,34) Cytotoxic effect of morin treated as a mixed micelle formulation was significantly increased compared with that of morin alone (Fig. 7A), suggesting the synergistic role of PluronicF127 and Tween80 as P-gp modulators.…”
Section: Discussionmentioning
confidence: 98%
“…Instead, TAB induced autophagic cell death in gastric cancer cells [ 40 ]. Recent evidence showed that TAB could sensitize breast cancer MDA-MB-231/Taxol cells to Taxol by increasing the intracellular accumulation of the chemo drug via abrogating the expression of major drug efflux P-gp protein [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…2013 ). P-gp was shown to be expressed in the cell lines used (MDA-MB-231; Zhang et al . 2014 ) and HeLa ( Al-Abd et al .…”
Section: Discussionmentioning
confidence: 99%